Changes in industry and corporate effects in the United States, 1978–2019 - Wang, Ming zhu (Strategic Management Journal, 2023)
Abstract Research Summary I present evidence of a shift in the relative contributions of industry and corporate effects to heterogeneity in business performance in the United States. In a systematic analysis of sequential timeframes between 1978 and 2019, I find a persistent rise in the explanatory power of corporate effects, which has grown to surpass that of industry effects. Consistent with these trends, I also find that an increasing share of multi‐business firms is operating only high‐performing or only low‐performing businesses, which coincides with refocusing efforts that began in the 1980s. This temporal perspective provides an explanation for why prior studies estimating industry and corporate effects have reached different conclusions. Managerial Summary I present evidence that how much industry and corporate parentage each matter to business performance among diversified firms in the United States has changed over time in a systematic way. Specifically, my analyses show that while factors at the industry level may have mattered more than those at the corporate level from the late 1970s through most of the 1990s, this has since reversed and corporate parentage likely explained more of business profitability throughout the 2000s and 2010s than industry membership. These changes coincide with a trend that began in the 1980s toward greater focus and relatedness among the operations of diversified firms.